Apie lietuvių senųjų raštų atoninę įvardžio formą te ‘tave’ - Razanovaitė, Auksė (Baltistica, 2010)
ABOUT THE ATONIC FORM OF 2 SG. ACC. te IN THE OLD LITHUANIAN TEXTSIn the old Lithuanian texts the atonic form gen., dat., acc. m(i), t(i) (Zinkevičius 1981, 49) is also used alongside the orthotonic genitive, dative and accusative forms of the first and the second person. The usual forms are mi, ti or the shortened ones -m or -t, except some forms te: used in the meaning of the second person accusative in the hymnal written by Saliamonas Mozerka Slavočinskis (SG) IOzapay pamażu / Meldźiute pamażu SG I 60,4–5, Sunau te girdźiu raudanti / Aſż ſaweſp tawe biłanti SG I 95,16–17 and Aß teyſingay ir łáymingay / Gȧrbinċiau te tułomis SG II 98,26–27. It is interesting that the clitic -te is used instead of the usual -ti in the old writings. The above-mentioned forms cannot be analysed apart from the reflexive particle, the origin of which is pronominal as well. Hermann is known to have paid attention to this phenomenon (1926, 83). It is thought that the reflexive particle se reflects the Baltic *s (Zinkevičius 1966, 331f.; Mažiulis 1959, 13; Rosinas 1995, 36). With reference to the form the Balts can be thought to have had other forms of accusative of pronominal clitics, such as *m, *t (Rosinas 1995, 36). Consequently, the forms with -te attested in the hymnal of Slavočinskis and in „Knyga nobažnystės“ show that the Baltic *t enclitic form te ‘tave’ is directly attested.
Keywords: lietuvių kalba; senieji raštai; klitikai; įvardžiai; isotrinė morfologija